(untitled) (Eurasian Medical Research Periodical, 2023)
One of the necessary drugs for the treatment of diabetic dyslipidemia affecting lipid metabolism is hydroxycis-methylglutaryl-coenzyme A-reductase inhibitors (statins) [2] and ezetimibe, which blocks the absorption of cholesterol in the epithelium of the small intestine, thereby preventing erythematic enterohepatic circulation of cholesterol [2,4]. Their effectiveness in correcting atherogenic dyslipidemia (DLP) and preventing macroangiopathies has been studied in patients with diabetes mellitus (DM). The aim of this study was to study the lipid-lowering efficacy of the combination therapy of rosuvastatin with ezithymibe in patients with type 2 diabetes mellitus